Understanding the importance of ICT driven information sharing in banking industry in India (International Journal of Food and Nutritional Sciences, 2022)
The changes brought about by digitalization have completely changed the banking industry and the way people deal with and do business with financial institutions. This study focuses on the United States of America and looks at how bank processes changed before and after they went digital. At first, putting banking activities on computers was a big step towards using technology, freeing up workers from doing too much manual work and making things run more smoothly. But it also showed some problems, such as methods that are easy to mess up and problems with managing data. After that, banks went digital to fix these problems by using technology to improve customer service, make operations run more smoothly, and add new services.